Aqeedah Values of Ahli Sunnah Waljama’ah in “Hikayat Tengkorak Kering”: A Content Analysis - Harapandi Dahri (Southeast Asian Journal of Islamic Education, 2022)
Aqeedah, fiqh, and akhlaq are the three main pillars in carrying out the religion that the Prophet has brought to the earth so that human beings can know their destiny perfectly. This matter has been recorded in the hadith of Jibril, which is a hadith that explains the arrival of the Angel Jibril to teach the pillars of religion to Muslims. The scholars describing the values of the three main teachings have various ways and methods. One of them is Haji Abdullah bin Haji Muhammad Sa'ed bin Haji Muhammad Arsyad who used the story entitled "Hikayat Tengkorak Kering" (dry skull tale). This article aimed to describe the aqeedah values of Ahli Sunnah Waljamaah found in the story “Hikayat Tengkorak Kering”. In order to understand aqeedah values embedded in this dry skull tale, this article employed a “content analysis” approach, which was by studying the content of the tale in-depth and linking it with authentic teaching sources (the Quran and al-Sunnah as well as interpretations of scholars of Ahli Sunnah waljama'ah). The data were in the form of written text from the story “Hikayat Tengkorak Kering”. The findings in this study are aqeedah values of Ahli Sunnah Waljama'ah such as faith in the Prophet of Allah, faith in the angels of Allah, faith in the Qada and Qadr, the realm of barzakh, the torment of the grave, hell and its torments, benefits of charity in the afterlife as well as practices that need to avoid in order to keep people away from the torment and punishment in hell.